Simulations on the reactive material projectile coated by explosively formed penetrator. (March 2020) - Ma, H B; Guo, H G; Su, Ch H; Zheng, Y F
Abstract: A typical shaped charge structure enhanced by reactive material projectile is established by AUTODYN-2D software. The formation and penetration processes of reactive inner core-wrapped compound EFP are simulated and analyzed. The results show that the segment liner with thick axis and thin edge becomes a penetrator with a lower velocity in the axis and a higher velocity in the edge under the shaped charge effects, which leads to EFP flipping forward and coating the reactive material projectile. The impacts between liner and reactive material projectile further increase the velocity difference between the axis and the edge, resulting in a better coating effect. The formation process is divided into three phases, including impact, coating and stretching. Then, the damage process contains penetration and deflagration of the following reactive material projectile. The liner thickness difference, curvature radius of the segment liner and radius of the reactive sphere all have important influences on formation and penetration of the reactive inner core-wrapped compound EFP.